Consumer Experiences with Gift Card Payment Scams: Causes, Consequences, and Implications for Consumer Protection - DeLiema, Marguerite (Victims & offenders, 2023)
Retail gift cards are requested by fraud perpetrators in many types of mass marketing scams because they are accessible to consumers and card values can be redeemed remotely and anonymously. We interviewed 27 individuals who experienced a gift card payment scam. Five themes emerged: (1) contexts of vulnerability, (2) cognitive and emotional dissociative states, (3) the mixed efficacy of retail interventions, (4) self-blame, and (5) consumer education and other safeguards. Contextual and situational factors, such as work stress, having a recent experience that corresponded with the premise of the scam, and having an unmet financial or socioemotional need, increased vulnerability. Perpetrators used strong emotional appeals to activate a stress response and to interfere with participants’ reasoned decision making. To prevent victimization, direct questioning by retail employees was less effective than outright refusals to sell them gift cards. Several participants reported severe emotional distress and symptoms associated with trauma following victimization. Participants did not hold the retail stores or gift card issuers accountable for their losses and instead expressed self-blame. They advocated for more consumer education about gift card payment scams as well as more empathy and support for victims.